BALANCE BETWEEN ETHICS AND LAW IN HEALTH PRACTICE - Widiyanto, Endra; Rofik Darmayanti (Journal of Hospital Management and Services, 2025)
In the world of health, service practices carried out by medical personnel and health professionals have a direct impact on human life. Therefore, health practices must be based on complementary ethical and legal principles. Ethics act as a moral guideline that directs health workers to be professional, fair, and respect patient rights. Meanwhile, the law provides binding rules to ensure that every medical action is carried out in accordance with established standards and protects the rights of patients and health workers. This study aims to provide a better understanding of how to maintain harmony between the two, so that it can support the creation of responsible, moral, and legal health practices. In this study using library materials, books, references, online media, print media as supporting materials for writing this scientific work. The method used in this study is using the normative legal method, namely a deductive study. In the deductive approach, theory is used as the beginning of answering research questions. The data sources used in this study are secondary legal materials and tertiary legal materials. Data collection techniques use literature studies, including documentaries. Data analysis is normative-qualitative by interpreting and constructing statements contained in documents and legislationThe results of the study are used as reading material that is useful for everyone so that they can learn and guide them to behave in everyday life in interacting with other communities. These health ethics and laws can be utilized optimally as guidelines and rules that regulate the procedures for a person to be able to prioritize politeness in the social life of society.